THE ROLE OF DIGITAL MARKETING COMMUNICATION OF AROMATHERAPY ALTERNATIVE MEDICINE IN INCREASING CONSUMER CONFIDENCE - Ramdan, Ahmad Taufiq Maulana; Tawaqal, Rizki Surya; Meltareza, Ridma (Journal of Business and Management Inaba, 2022)
Communication is an important marketing techniques in promoting alternative treatment, products and services since years a go people have interact through communication serve the needs of basic human, of interacting the act of conveying information to another individual to influence the, , opinion or their behavior, either directly or indirectly through. mediaWith the use of communications technology, people now can communicate more efficient not only with those who live nearby but also across great distances by storing and send a message or information. The technologies used in communication is a tool , the structure of the organization , and social norm faced by people when gather , process , and exchange information with others .Platform social media that is ideal for marketing communications one of them is instagram .In their aromaterapisehat use instagtam with account names @ aromaterapisehat , and communication marketing that he did. This study attempts to find out how the role of marketing communications digital alternative medicine aromatherapy to increase consumer confidence. Methods used in this research is qualitative whose aim is to explore in depth a phenomenon. The result of digital communication marketing research is done by a aromaterapisehat excellent in used by the digital media instagram to communicate all kinds of information and knowledge about products they sell aromaterapi so consumers easy understand about all sorts of the advantages and disadvantages of and how to benefit from the product of a most aromaterapisehat and true.